2017
DOI: 10.1016/j.nicl.2017.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Altered functional brain connectivity in patients with visually induced dizziness

Abstract: BackgroundVestibular patients occasionally report aggravation or triggering of their symptoms by visual stimuli, which is called visually induced dizziness (VID). These patients therefore experience dizziness, discomfort, disorientation and postural unsteadiness. The underlying pathophysiology of VID is still poorly understood.ObjectiveThe aim of the current explorative study was to gain a first insight in the underlying neural aspects of VID.MethodsWe included 10 VID patients and 10 healthy matched controls, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 79 publications
1
60
1
1
Order By: Relevance
“…From posturographic studies and gait analyses it is known that PPV patients exceedingly rely on visual input during standing and walking . Patients with visually induced dizziness, also known as visual vertigo, also show an increased connectivity between thalamus, occipital cortex, and cerebellar areas . Furthermore, during a self‐motion simulation in PPPD patients higher dizziness handicap values correlated positively with occipital activity .…”
Section: Discussionmentioning
confidence: 99%
“…From posturographic studies and gait analyses it is known that PPV patients exceedingly rely on visual input during standing and walking . Patients with visually induced dizziness, also known as visual vertigo, also show an increased connectivity between thalamus, occipital cortex, and cerebellar areas . Furthermore, during a self‐motion simulation in PPPD patients higher dizziness handicap values correlated positively with occipital activity .…”
Section: Discussionmentioning
confidence: 99%
“…The first neuroimaging studies of visual vertigo,41 chronic subjective dizziness2 and PPPD42 suggest that there may be an additional pathophysiological mechanism underlying PPPD, namely a deficiency in cortical processes that subserve locomotion and spatial orientation at the highest levels. Although the research paradigms differed from one another and the use of imaging techniques for studying PPPD is just getting started, a pattern of results is beginning to take shape.…”
Section: Pathophysiologymentioning
confidence: 99%
“…Another study (Van Ombergen et al, 2017) reported increased connectivity in visual cortical areas and decreased connectivity in vestibular cortical areas using a resting state fMRI in patients with visuallyinduced dizziness, but did not account for the psychiatric state of their subjects. Taken together, our results and the findings of these two previous studies indicate that alterations in brain functioning attributable to PPPD itself are decreases in connectivity among the vestibular and visual cortices, the frontal regulatory regions and the hippocampus.…”
Section: Group Differences In Functional Connectivity After Controlmentioning
confidence: 99%